2010
DOI: 10.4067/s0718-58392010000400008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vermicompost and Compost on Lettuce Production

Abstract: A greenhouse study was conducted to evaluate the effect on total growth and leaf nutritional content in lettuce (Lactuca sativa L.) in the Agrotechnology Sciences Department of the Universidad Autonoma de Chihuahua, Mexico in 2007. Three types of fertilization treatments were analyzed: two organic and one conventional or inorganic. Both vermicompost and compost were produced from cattle manure in a 25-wk process. The study included 12 experimental units made up of lettuce plantlets var. Great Lakes. A linear m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
33
6
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 11 publications
12
33
6
3
Order By: Relevance
“…A very important aspect in the production of potted ornamental plants is the controlled and induced vegetative and floral growth by horticultural practices. Many studies on the use of organic or inorganic components for enhanced growth in soilless cultures have been reported by researchers (Ribeiro et al, 2007;Zaller, 2007;Arancon et al, 2008;Bustamante et al, 2008;Bachman and Metzger, 2008;Medina et al, 2009;Hernández et al, 2010;Ntoulas et al, 2011). Arancon et al (2008) reported that petunia seeds germinated faster in growth substrates with larger amounts of vermicomposts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A very important aspect in the production of potted ornamental plants is the controlled and induced vegetative and floral growth by horticultural practices. Many studies on the use of organic or inorganic components for enhanced growth in soilless cultures have been reported by researchers (Ribeiro et al, 2007;Zaller, 2007;Arancon et al, 2008;Bustamante et al, 2008;Bachman and Metzger, 2008;Medina et al, 2009;Hernández et al, 2010;Ntoulas et al, 2011). Arancon et al (2008) reported that petunia seeds germinated faster in growth substrates with larger amounts of vermicomposts.…”
Section: Discussionmentioning
confidence: 99%
“…Growers typically use peat, perlite, vermiculite, sand, fallow land, and various organic and inorganic composted materials to prepare nutritious mixtures for floricultural plant production. Currently, in the entire world, different composting technologies are used for plant production; these are based on several types of wastes such as: municipal organic waste, sewage sludge, agricultural waste, animal manures, and some sorts of industrial waste (Castaldi et al, 2005;Tognetti et al, 2007;Hernández et al, 2010;Ntoulas et al, 2011). Humic acids are one of the natural organic compounds from the soil or composted materials which are included in growth substrates to increase substrate fertility, growth and yield for horticultural crops (Atiyeh et al, 2002;Arancon et al, 2006;Campitelli and Ceppi, 2008;Ahmad et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…There are many advantages that can arise from composting, including the reduction of volume, weight and water content of the waste as well as producing inactive pathogenic organisms [8,9]. Therefore, the compost can contribute to the improvement of soil contents and nutrients required for harvesting plants, and will significantly reduce the use of synthetic fertilizers [10]. The application of compost can improve soil properties that are badly in need of renewal as it can increase the organic carbon contents in the soil.…”
Section: Introductionmentioning
confidence: 99%
“…However, negative impacts of excessive use of chemical products in agriculture have been appeared, especially, on human health. Besides human health, intensive chemical uses decreased soil fertility and caused serious environmental problems such as oil and groundwater pollution, salinization and desertification (Hernández et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Successful crop cultivation mostly depends on proper plant nutrition (Hernández et al, 2010). Conventional farming still relies heavily on chemical inputs such as synthetic fertilizers and pesticides (Lampkin, 1990).…”
Section: Introductionmentioning
confidence: 99%